PERAN PENGENDALIAN VISUAL BERBASIS 5S DALAM MENGURANGI PEMBOROSAN WAKTU PADA OPERASI GUDANG - Muhammad Aditya; Enda Permana; Vina Dwiyanti (Inaque : Journal of Industrial and Quality Engineering, 2026)
Warehouse operations play a critical role in logistics systems but are often a major source of waste, particularly Pemborosan waktu caused by searching activities and unclear workflows. From a lean logistics perspective, eliminating non-value-added activities is essential to improve operational efficiency. Pengendalian Visual, commonly implemented through the 5S (seiri, seiton, seiso, seiketsu, dan shitsuke) method, is widely recognized as an effective approach to address these issues. This article aims to evaluate the contribution of 5S-based Pengendalian Visual to the reduction of Pemborosan waktu in warehouse operations, with a particular focus on searching time, through the analysis of empirical findings from previous studies. A narrative literature review was conducted by analyzing relevant studies in the fields of lean logistics and warehouse management. The findings indicate that Pengendalian Visual enhances visual clarity, accelerates picking processes, and reduces searching time. This review also identifies research gaps related to the standardization of Pemborosan waktu measurement and the shitsukeability of 5S implementation.